In depth: Ocean science: Youth dive in! - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2025)
Launched in 2021, the Environmental DNA (eDNA) Expeditions[1] have allowed to mobilize hundreds of students and schoolchildren across marine World Heritage sites to collect water samples with kits for recording species’ presence. The goal is to study the impacts of climate change among global marine biodiversity hotspots. A second phase of the eDNA project was launched in June 2025.